Substantiation of methods for constructing engineering networks of operating industrial enterprises - Ishchenko, O.; Donenko, I. (Ways to Improve Construction Efficiency, 2018)
The reconstruction of industrial enterprises differs significantly from the new construction and has its own peculiarities in the design, the development of the technological process of construction, the specifics of construction and installation work, which is associated with the constraints of the construction site, the need for step-by-step execution of work at different sites, the combination of the enterprise's production activities with the construction- installation works, dismantling, in some cases, old engineering networks or parts thereof. The article analyzes the existing methods of constructing utility networks, identifies the advantages and disadvantages of these methods, the specifics of use in cramped conditions and the appropriateness of using it in restoring networks at operating industrial enterprises.